Canine Chronic Inflammatory Enteropathy with Special Reference to Immunological Markers for Diagnosis (London Journal of Medical and Health Research, 2025)
A study on Chronic Inflammatory Enteropathy (CIE) in dogs was conducted at Madras Veterinary College Teaching Hospital. Out of 40 dogs with persistent gastrointestinal signs, 16 were diagnosed with idiopathic CIE. The condition was more prevalent in 2-5 year-old male dogs, particularly in mongrel breeds. Clinical signs included chronic diarrhoea, vomiting, and weight loss, with disease duration of 1-3 months. Gastroduodenoscopy revealed hyperemia, friability, and granularity in the stomach and duodenum, while colonoscopy showed friability, hyperemia, ulceration, and discoloration of colonic mucosa. Histopathology of duodenal biopsies showed villous stunting, mucosal fibrosis, and lymphoplasmacytic infiltration. Immunohistochemistry indicated upregulation of CD3+ cells and Ki67 antigen. A positive correlation was found between the Canine Chronic Enteropathy Activity Index (CCECAI) and endoscopic and histopathological scores.
Keywords: Quality improvement; brazil; organ transplantation; management program; PAT-MA; health systems; Maranh; pulmonary hypertension.; Chronic thromboembolic pulmonary hypertension; Thrombendarterectomy; Pulmonary vascular resistance; Long-term medical history.; HIV; cervical cancer; Screening; CIN; HPV; Togo.; Tokophobia; Developmental trauma; Cognitive-behavioral therapy; Reproductive mental health; Cultural psychiatry; Enteropathy; CCECAI score; Immunohistochemistry; CD3+positive cells